Effect of Two Years of Conservation Agricultural Practices on Weed Seed Banks Evaluated Using Three Techniques - Otim, Godfrey Anyoni; Ocan, David; Kumakech, Alfred; Tumwebaze, Susan; Obia, Alfred (East African Nature and Science Organization, 2024)
Understanding the soil seed bank is very important when developing integrated weed management technologies and detecting the influence of crop management practices on weeds. In conventional weed control, farmers tend to focus on the above-ground, yet the above-ground vegetation is related to the below-ground soil seed bank. Several soil seed bank estimation methods have been used to estimate the soil seed bank, but varying results have been obtained under different field management practices and soil depths. In this study, we compared three methods for estimating the soil seed bank: seedling emergence method and two direct seed extraction methods (floatation and cloth bag) for determining weed seed density and diversity from different soil depths under conservation farming practices. The three methods had significant differences in estimating weed densities from the soil seed bank (p<0.001). The greenhouse seedling emergence method had a mean number of 5.06, cloth bag had 4.07 while floatation method had the lowest number of 3.38 per 300g of soil. The mean highest weed density was obtained from soil depth of 0-15 cm (5 weeds/300g vs 1.6 weeds/300g of soil from 15-30 cm depth). For soil seed bank diversity, cloth bag method had the highest mean value followed by greenhouse emergence and lastly floatation method with Simpsons diversity index of 2.72, 1.79 and 1.31, respectively. Shannon Weiner diversity index followed the same pattern for the three methods. The methods had different sensitivity to density and diversity and therefore greenhouse emergence method should always be combined with cloth bag method. The greenhouse emergency method detected a total of 26 weed species, cloth bag detected 22 weed species and Floatation method detected 18 weed species. Despite, the greenhouse emergence method detecting more species than the cloth bag at 26 and 22 weed species, respectively, it had a lower Simpson’s diversity index than the cloth bag method due to lower species evenness. Sampling of the entire soil plough layer of 0-30 cm depth for disturbed agricultural soils may produce the best results. Seasons significantly influenced soil seed bank diversity and not soil seed bank density where second season (B) significantly increased soil seed bank diversity. Soil cover practice through intercropping maize with soybean significantly reduced soil seed bank density and not diversity in both minimum and conventional tilled plots. This positive influence on weed density and diversity is a good indicator for integration into a weed management program